Inequalities in emerging economies Informing the policy dialogue on inclusive growth - Balestra, Carlotta (OECD Statistics Working Papers, 2018)
The paper describes inequality trends in selected emerging economies (Brazil, Colombia, Costa Rica, China, India, Indonesia and South Africa) in a range of monetary (i.e. income) and non-monetary dimensions of people's life (i.e. education, health status, employment and subjective well-being). Inequalities are analysed not only in terms of overall dispersion, but also as gaps between population groups defined by specific characteristics (i.e. sex, age, educational attainment and place of living). To the extent made possible by the nature of available data, measures of income inequality for these emerging countries, as well as for 7 Latin American countries (Bolivia, Dominic Republic, Ecuador, Panama, Paraguay, Peru and Uruguay), are based on concepts and definitions similar to those used by the OECD for its member countries. All the emerging economies covered in the paper show levels of income inequality higher than in the five most unequal OECD countries, while the picture is more mixed when it comes to inequalities in other dimensions of people's well-being. An annex complements the analysis by presenting an assessment of the quality of the available data on income distribution for the emerging countries covered in the paper